Stability Indicating RP-HPLC for Quantification Mangiferin in Extract of Three Species Mango Leaves - Retnaningtyas, Yuni; Kristiningrum, Nia; Renggani, Hidayah Dwi; Sary, Indah Purnama (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
The stability indication of Reversed Phase-High Performance Liquid Chromatography (RP-HPLC) method was validated for quantitative determination of mangiferin on three species mango leaves (Mangifera odorata Griff, Mangifera foetida Lour, and Mangifera indica L.). The samples were extracted by maseration method using methanol and concentrated using rotary evaporator. The method carried out on stationary phase a purospher RP-18 endcapped (25 cm × 4.6 mm i.d., 5 µm) column with a mobile phase consisting of methanol: phosphoric acid 0.1% (v/v) (31:69); flow rate:0.8 mL/min; solvent methanol, detection was carried out at 258 nm. The analytical performace this measurement is good with the value of linearity (r2=0.998), precision (%RSD=0.649%), and accuration (10.67%). The forced degradation studies were carried out according to the International Conference on Harmonization (ICH) guidelines. The results indicating that the complete separation between degradation products and mangiferin peak occured. The degradation limit of mangiferin 5–20% (according to the guideline of ICH) except in basic condition (100%). The method was succesful applied to determine of the mangiferin in pakel (Mangifera foetida), kweni (Mangifera indica) and kopyor (Mangifera odorata) extract. The mangiferin content was obtained are pakel (9.95%), kopyor (7.40%) and kweni (Mangifera odorata) (2.49%) respectively.